OPTIMAL LOAD DISPATCHING THROUGH WIND ENERGY AND SOLAR ENERGY SYSTEMS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Conventional resources of energy such as coal and fossil fuels are now beingreplaced with renewable sources. Solar PV and wind energy conversion systems arebeing widely employed for harvesting electric energy. Modern power electronicconverters have made it possible to draw maximum power from these solar and windenergy conversion systems. This paper presents a hybrid energy system that integrateswind energy from Permanent Magnet Synchronous Generator (PMSG) and aphotovoltaic (PV) solar system. Maximum Power Point Tracking (MPPT) algorithm isimplemented that extracts maximum power from PV array under constantly changingenvironmental conditions. The outputs of wind turbine and PV array are integratedsuitably in order to retain continuous power supply as per load requirement. Operationof wind generator is mainly determined by estimation of speed which is carried out by asensor-less rotor speed estimator. This estimator replaces all mechanical sensors andthey are no longer needed. The turbine speed is thus governed based on the estimatedrotor speed by controlling the voltage and current at the input of Boost converter. Theproposed system is designed and simulated on Matlab / Simulink platform and resultsare discussed.